Sensitivity to Sound in Web-Based FPS Game - Pasila, Agustinus Altrian Fajar; Nugroho, Erdhi Widayarto; Prasetya, FX Hendra (Journal of Business and Technology, 2024)
To train the hearing of individuals, both those with and without visual impairment, in a fun and effective way, the research methods used in this study include needs analysis, design, implementation, and testing. The result of this research is a web-based game that can be used to train an individual's hearing in a fun and effective way. The results of this study show that the developed web game can be used to train an individual's hearing in a fun and effective way. This game is equipped with various playing methods, each of which has several levels that can be accessed according to the level of difficulty, making it suitable for individuals with different levels of hearing ability.